A dual chromophore sensor for the detection of amines, diols, hydroxy acids, and amino alcohols. Issue 31 (28th March 2019) - Pushina, Mariia; Farshbaf, Sepideh; Shcherbakova, Elena G.; Anzenbacher, Pavel
Abstract : The determination of enantiomeric excess (ee) in various groups of chiral compounds, namely amines, amino alcohols, diols, and hydroxy acids is performed using a dual chromophore FRET/PET based sensor ensemble. Abstract : The determination of enantiomeric excess (ee) in various groups of chiral compounds, namely amines, amino alcohols, diols, and hydroxy acids is performed using a dual chromophore FRET/PET based sensor ensemble. The sensing ensemble utilizes fluorescence changes from two chromophores (indicators) to classify 13 pairs of enantiomers as well as allows for the qualitative and quantitative determination of ee of various classes of chiral compounds with high accuracy (<2% error).